From Molecular‐Level Organization to Nanoscale Positioning: Synergetic Ligand Effect on the Synthesis of Hybrid Nanostructures. (12th October 2017) - Xiang, Di; Liu, Hong; Yang, Lei; Liang, Yuting; Zhu, Jiaqi; Lu, Zhongyuan; Hou, Ying; Yang, Ming
Abstract: A key challenge in advancing the design of hybrid nanostructures (HNs) lies in the difficulty in mastering the principle of selected hybrid formation, which is complicated not only by the size and shape variations of nanoparticles but also by the interfacial phenomena associated with surface ligands. Here this study elaborates the formation mechanism of HNs by a combined experimental and theoretical study employing multiscale simulations and shows how molecular information encoded on particle surface can be transferred into distinct composite patterns. The emergence of different HNs is found to be not only related to ligand binding strengths affecting the reaction kinetics but also the ligand–ligand interactions responsible for phase segregation. Unexpectedly, the sulfidation of Ag nanoparticles co‐stabilized by citrate/gallic acid with different molar ratios constantly produces heterodimers with faster reaction rate than the formation of core–shell structures when they are solely coated by citrate or gallic acid. The surprising result originates from the phase separation of two short surface ligands with large contrast in binding strengths as indicated by photoluminescence spectra and supported by the dissipative particle dynamics simulations. Hierarchical HNs consisting of a heterodimer shell with built‐in hot spots can be further synthesized using Au@Ag core–shell particles with mixed surface layers. Abstract : Synergetic ligand effect on the formation of hybrid nanostructures is revealed by a combined experimental and theoretical study, allowing the establishment of the connection between molecular‐level organization and nanoscale positioning. The demonstrated dual ligand roles originating from different binding strengths and ligand–ligand interactions responsible for phase segregation pave a way for advancing the design of functional inorganic composite materials.